O estudo de prismas a partir da utilização do modelo Van Hiele em um contexto de aprendizagem baseada em problemas com apoio das tecnologias digitais - Picinin, Elisandra (2020)
Due the problems in teaching and learning process in Geometry content, the teacher needs to propose strategies and methodologies that instigate and encourage student´s curiosity. Therefore, it is essential understand how the development of geometric thinking works, logical-mathematical reasoning and the capacity to elaborate systematized concepts. Currently, teaching practices have been continuously questioned in consequence of several factors, in particular, disregarding student´s demands, globalized, technological world and abundance information and even due to the teacher´s own lack unpreparedness methodological regarding different methodological. In this sense, the research question that this text is dedicated: What is the influence of active methodologies and digital Technologies for the development of Prisms content in high school students? Before this context, seeks to present a teaching and learning proposal that serves as a didactic resource for a critical, creative and reflective education of the student. Through a biographical review, it is intended to explore the possibilities of active methodologies associated with technological resources for learning geometry. This dissertation is also comes with an Education Product created from theoretical premises of this dissertation and applied to a group of high school students. For the records of practical activity, were used dialogues, information and notes from the logbook made by students as well as the logbook developed by the researcher. It was verified through the application of the didactic sequence, using the Van Hiele model, the process of raising the student´s level of geometric thinking. For that, it was considered the development of the proposed activities and evolution that the students presented during the application of the same. The research presented was a qualitative and quantitative approach and intervention. Can be concluded, therefore based on the experiences Van Hiele, that after the application of the educational product, students researchers have significantly evolved their level of Geometric Thinking. Also it was evidenced that the use of the Active PBL Methodology and digital technologies made possible besides a participative and creative learning, a successful alternative for learning Prism content. This dissertation accompanied an Educational Product available in